Higher Oxygen Content Affects Rabbit Meat’s Quality and Fatty Acid Profile in a Modified Atmosphere - Joanna Składanowska-Baryza; Dominik Kmiecik; Magdalena Rudzińska; Annalisa Vissio; Anna Grygier; Agnieszka Ludwiczak; Marek Stanisz (International Journal of Food Science)
After 7 days of storage, the quality of the meat packed in both systems (MAP and VAC) was satisfactory; however, after 14 and 21 days, there was a noticeable decline in quality, as evidenced by changes in the water percentage and color parameters (L∗, a∗, and b∗). However, muscles stored in the MAP1 had the highest tenderness. The results indicated that as the storage time increased (up to 21 days), the share of C14:0 (P<0.001) and C16:0 (P<0.001) acids in the fat of the LTL muscles decreased. Only the share of C18:0 (P=0.001) and C20:1 (P=0.015) acids was significantly influenced by the packaging method. The highest iodine level was found in MAP1 21 days after packaging (85.68). The ratio of n-6/n-3, PUFA/SFA, AI, and TI indexes, which indicate a higher nutritional quality of fat, varied only with storage time without being affected by the gas mixture (P>0.05). The H/H level differed significantly with the storage time (P<0.001), with no effect of the gas mixture (P=0.133). After the 21-day storage period, the controlled atmosphere led to an increase in the concentration of MUFA and PUFA and a decrease in SFA, according to the study of the fatty acid profile.